Antioxidant, anti-inflammatory and anti-proliferative effects of methanolic leaf extract of Muntingia calabura L. on colon cancer - Md Nasir, Nur Liana (2017)
Worldwide known as ‘Jamaican cherry’ and to the Malay as ‘kerukup siam’, Muntingia calabura is not fully utilized in the Malay traditional medicine, despite the medicinal uses of various part of this plant by other tribes. The present study evaluated the cytotoxicity of methanol extract of M. calabura leaves (MEMC) towards human colorectal cancer cell line (HT-29) and cancer chemopreventive property of this extract. MEMC was partitioned into 3 partitions: petroleum ether extract (PEMC), ethyl acetate extract (EAMC), and aqueous extract (AQMC). All these extracts underwent antioxidant study using 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay (DPPH), superoxide dismutase scavenging activity assay (SOD), oxygen radical absorbance capacity assay (ORAC) and total phenolic content (TPC). MEMC were screened for cytotoxicity towards HT-29 and 3T3 cell lines using MTT assay. The anti-inflammatory study using lipoxygenase (LOX) and xanthine oxidase (XO) assays was also performed. For in vivo, assessment of toxicity of MEMC at 50, 250 and 500 mg/kg was done for 90 days of oral administration in male Sprague Dawley rats. The parameters for toxicity include changes of body weight, relative organ weight, haematological and biochemical profile, and gross histology of vital organs. In chemopreventive study, rats were randomly divided into 5 groups of 7 rats (two control groups and 3 treatment groups). All group received azoxymethane (AOM) injection (15 mg/kg) except for the group 1 (Normal control). Rats in treatment groups (group 3, 4 and 5) received 50, 250 and 500 mg/kg of MEMC, while rats in AOM control (group 2) only received AOM injection. Rats were euthanized after 8 weeks of treatment. Further evaluation on MEMC partition extracts was done using in vitro model. All the partitions (PEMC, EAMC and AQMC) were tested against HT-29 cell line and anti-inflammatory study. The induction of apoptosis was further confirmed by examining the morphological changes of cells under phase contrast field of fluorescent microscope and staining using acridine orange/propidium iodide. The extracts were screened on the bioactive compounds that are responsible for pharmacological properties using high performance liquid chromatography (HPLC). From the antioxidant assays, MEMC and EAMC demonstrated strongest activity in SOD, DPPH and TPC assay. In vitrostudy of MEMC showed inhibition against HT-29 cells withIC50 of 90.8±5.8 μg/mL. Nevertheless, MEMC also showed strong anti-inflammatory action against LOX activity with inhibition of 87.65±4.21% and moderate inhibition against XO, 51.89±4.58%. In toxicity study, The No Observed Adverse Effect Level (NOAEL) for MEMC was greater than 500 mg/kg. For chemoprevention study, MEMC significantly reduced the number of aberrant crypt foci (ACF) (p < 0.05) ranging from 20.77%, 29.43% and 55.13% in rats fed with 50, 250 and 500 mg/kg of MEMC, compared to the AOM control group. For antioxidant assay, treatments with 500 mg/kg of MEMC significantly increase all antioxidants level with 2.526±0.0878U/g tissue for SOD, 108.1±4.942U/g tissue for CAT and 32.06±1.782 mM/g tissue for GSH as compared to the AOM control group. Among MEMC partitions, EAMC showed highest cytotoxicity effect towards HT-29 with IC50 of 58±12.9μg/mL and HT-29 cells exhibitcharacteristics of apoptosis such as cell membrane blebbing and cell membrane rupture after stained with AO/PI. Phytochemical screening and HPLC analysis demonstrated the present of flavonoid-based compounds in MEMC and EAMC namely rutin and quercetin. In conclusion, MEMC exerted potential anti-colon cancer activity that partly attributed to its antioxidant and anti-inflammatory activity. EAMC was considered to have the best activity among partition extracts, which warrant further investigation such as in vitro study to confirm mode of cell death, in vivo chemoprevention study and isolation of bioactive compounds.